The taxable basis of the sales tax, always special - Hernández Belaides, Hernán José; Hernández Belaides, Hernán José (Corporación Universitaria Americana, 2020)
The taxable base of the sales tax constitutes a normative labyrinth generated by the diversity of taxable bases in this tax. Although it is true that only a special taxable base of VAT is stated in the Tax Statute, it is also true that each transaction has, and requires, the exact determination of a special taxable base for the correct liquidation of the tax, therefore, This research aims to highlight the importance of the assumption of taxable bases to cause the tax. The methodology used is deductive through the analysis of the rules and laws that regularize sales tax and documents and jurisprudence associated with the subject.